Web-based Library Information System at SMK PGRI Sukodadi Lamongan - Annas Susanto, Fajar; Herlambang, Teguh; Yudianto, Firman; Wulan, T D; Ningsih, P R; Permatasari, A I (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of school library as a place to read is now less and less desirable by students to read books and search for scientific literature, this is because it is defeated by information media such as the internet which is easier to use in searching for various kinds of knowledge and reading sources. The impact of the information media is also experienced by the SMK PGRI Sukodadi Library which has a large collection of books that should be used by students to support learning activities but students are less interested in reading and borrowing books from the library in addition to having certain assignments from the teacher that require students to borrow books. from the library. Seeing the problems above, a website-based library information system design is made and the development of a library management information system at SMK PGRI Sukodadi Lamongan.